1968
DOI: 10.1002/pol.1968.150060711
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of cyclic iminoethers. V. 1,3‐oxazolines with hydroxy‐, acetoxy‐, and carboxymethyl‐alkyl groups in the 2 position and their polymers

Abstract: Oxazolines containing carbomethoxy‐, acetoxy‐, and hydroxy‐alkyl groups on the side chain were prepared and polymerized. The properties of the polymers were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 5 publications
0
60
0
1
Order By: Relevance
“…A number of studies have been reported on the polymerization of 2-alkyl-2-oxazolines containing pendent functional groups, including alkene, [11][12][13][14] alkyne, [14,15] acetoxy, [16] N-Boc-amine, [17] acetal, [18] carbazol, [19,20] , phenyliodide, [21] and azide. [14] The palette of functional side chains can then be widely extended, virtually to any kind of functionality, by applying polymer analogue reactions (!…”
Section: Macromolecular Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have been reported on the polymerization of 2-alkyl-2-oxazolines containing pendent functional groups, including alkene, [11][12][13][14] alkyne, [14,15] acetoxy, [16] N-Boc-amine, [17] acetal, [18] carbazol, [19,20] , phenyliodide, [21] and azide. [14] The palette of functional side chains can then be widely extended, virtually to any kind of functionality, by applying polymer analogue reactions (!…”
Section: Macromolecular Engineeringmentioning
confidence: 99%
“…[14] The palette of functional side chains can then be widely extended, virtually to any kind of functionality, by applying polymer analogue reactions (! hydroxy, [16] amine, [17] aldehyde, [18] and triphenylphosphine [21] ) and ''click'' modifications (thiol-ene [13] and azide-alkyne [15] ).…”
Section: Macromolecular Engineeringmentioning
confidence: 99%
“…Furthermore, numerous functional monomers allow the introduction of pendant functional side chains. Among others, carboxylic acid, [3,4] hydroxyl [3,5] and, more recently, amine, [6] thiol, [7] aldehyde [8] and alkyne [9] side chains are of particular interest for preparation of poly-and multifunctional polymer carriers for biomedical applications. Furthermore, the CROP of 2-oxazolines allows for the preparation of telechelics, [9,10] (multi)block-copolymers [11] or surface reactive lipopolymers.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the ester can be hydrolyzed to the corresponding carboxylic acid providing a versatile handle for conjugation as well as a means to introduce pH responsiveness. Although the potential of side-chain methyl ester-containing PAOx copolymers is well established, there is remarkably little known about their thermal features and thermoresponsive behavior [33,[43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…Functional groups, often protected, can be introduced into PAOx by making use of a functional monomer or initiator during the living cationic ring opening polymerisation (CROP, Scheme 1) of 2-oxazoline monomers or by using a functional terminating agent, yielding well-defined PAOx with control over number and type of functionalities [15,[29][30][31][32][33][34][35][36][37][38]. Methyl esters are especially interesting, because they can undergo a direct amidation with a variety of amines to easily introduce other functional groups such as alcohols, hydrazide and amines [39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%